Profitability of sandbar cropping method of pumpkin cultivation in char land areas of northern Bangladesh - Khatun, M; Rashid, MA; Miah, MAM; Khandoker, S; Islam, MT (Bangladesh Journal of Agricultural Research, 2018)
The study was undertaken to find out the profitability and export potentialities of pumpkin cultivation in the char lands of Rangpur and Gaibandha district of Bangladesh. A total of 120 pumpkin growers taking 60 farmers from each district were randomly selected for the study. Descriptive statistics was used to analyze cost and return of pumpkin. The Cobb-Douglass production function was used to estimate the coefficients of the various variables analysed and MPP, MVP and resource use efficiency were also used to estimate the efficiency of resource use in the study area. The study revealed that net returns were positive for pumpkin cultivation. However, the higher net return was estimated for Rangpur district (Tk 105,299/ha) compared to Gaibandha (Tk.93, 936/ha). Bangladesh had comparative advantage for producing pumpkin as the estimates of domestic resource cost (DRC) was less than one. The value of DRC for pumpkin was less than unity implied that the production of pumpkin would be highly efficient for export promotion. The estimated results of the Cobb-Douglass production function showed increasing returns to scale. The results of the efficiency computation indicated that inputs were underutilized. Farmers in the study area used too little input to cultivate pumpkin that means the cost of using inputs is less than the value of marginal product. This suggests that farmers can incur more cost for these inputs to be efficient and then production will be increased. Bangladesh J. Agril. Res. 42(4): 647-663, December 2017